Improving regional ozone modeling through systematic evaluation of errors using the aircraft observations during the International Consortium for Atmospheric Research on Transport and Transformation - Marcelo Mena_Carrasco; Youhua Tang; Gregory R. Carmichael; Tianfeng Chai; Narisara Thongbongchoo; J. Elliott Campbell; Sarika Kulkarni; Larry Horowitz; Jeffrey Vukovich; Melody Avery; William Brune; Jack E. Dibb; et al. (My University, 2007)
During the operational phase of the ICARTT field experiment in 2004, the regional air quality model STEM showed a strong positive surface bias and a negative upper troposphere bias (compared to observed DC‐8 and WP‐3 observations) with respect to ozone. After updating emissions from NEI 1999 to NEI 2001 (with a 2004 large point sources inventory update), and modifying boundary conditions, low‐level model bias decreases from 11.21 to 1.45 ppbv for the NASA DC‐8 observations and from 8.26 to −0.34 for the NOAA WP‐3. Improvements in boundary conditions provided by global models decrease the upper troposphere negative ozone bias, while accounting for biomass burning emissions improved model performance for CO. The covariances of ozone bias were highly correlated to NO z , NO y , and HNO 3 biases. Interpolation of bias information through kriging showed that decreasing emissions in SE United States would reduce regional ozone model bias and improve model correlation coefficients. The spatial distribution of forecast errors was analyzed using kriging, which identified distinct features, which when compared to errors in postanalysis simulations, helped document improvements. Changes in dry deposition to crops were shown to reduce substantially high bias in the forecasts in the Midwest, while updated emissions were shown to account for decreases in bias in the eastern United States. Observed and modeled ozone production efficiencies for the DC‐8 were calculated and shown to be very similar (7.8) suggesting that recurring ozone bias is due to overestimation of NO x emissions. Sensitivity studies showed that ozone formation in the United States is most sensitive to NO x emissions, followed by VOCs and CO. PAN as a reservoir of NO x can contribute to a significant amount of surface ozone through thermal decomposition.
Keywords: Tropospheric ozone; Atmospheric chemistry and aerosols